This life I've led; my autobiography - Zaharias, Mildred Babe Didrikson, 1913-; Paxton, Harry T. (New York, Barnes, 1955)
The true story of the Babe's remarkable sports career is combined in her autobiography with loving glimpses of her Norwegian-born parents and happy family life in Beaumont, Texas, candid recollections of her romance and marriage with George Zaharias, and an account of her determined struggle to overcome a serious cancer operation in 1953.
13 28
Keywords: Zaharias, Mildred Babe Didrickson, -- 1913-; Golf-females